Combining two filter paper‐based analytical methods to monitor temporal variations in the geochemical properties of fluvial suspended particulate matter. Issue 13 (11th July 2013) - Cooper, R. J.; Rawlins, B. G.; Lézé, B.; Krueger, T.; Hiscock, K. M.
Abstract Many of the commonly used analytical techniques for assessing the properties of fluvial suspended particulate matter (SPM) are neither cost effective nor time efficient, making them prohibitive to long‐term high‐resolution monitoring. We present an in‐depth methodology utilizing two types of spectroscopy which, when combined with automatic water samplers, can generate accurate, high‐temporal resolution SPM geochemistry data, inexpensively and semi‐destructively, directly from sediment covered filter papers. A combined X‐ray fluorescence spectroscopy and diffuse reflectance infrared Fourier transform spectroscopy approach is developed to estimate concentrations for a range of elements (Al, Ca, Ce, Fe, K, Mg, Mn, Na, P, Si, Ti) and compounds (organic carbon, Aldithionate, Aloxalate, Fedithionate, and Feoxalate) within SPM trapped on quartz fibre filters at masses as low as 3 mg. Calibration models with small prediction errors are derived, along with mass correction factor models to account for variations in retained SPM mass. Spectral pre‐processing methods are shown to enhance the reproducibility of results for some compounds, and the importance of filter paper selection and homogeneous sample preparation in minimizing spectral interference is emphasized. The geochemical signal from sediment covered filter papers is demonstrated to be time stable enabling samples to be stored for several weeks prior to analysis. Example results obtained during a heavy precipitation event in October 2012 demonstrate the methodology presented here has considerable potential to be utilized for high‐resolution monitoring of SPM geochemistry under a range of in‐stream hydrological conditions. Copyright © 2013 John Wiley & Sons, Ltd.